Formulasi Bakteri Endofit Untuk Menekan Kejadian Penyakit Fusarium Pada Padi Beras Merah (Oryza nivara. L) - Ahmad Khairil Anam; Mariana Mariana; Ismed Setya Budi (JURNAL PROTEKSI TANAMAN TROPIKA, 2024)
This research aims to study the effect of peat soil endophytic bacterial formulations, lowland swamp soil endophytic bacterial formulations, tidal swamp soil endophytic bacterial formulations, kelakai endophytic bacterial formulations on red rice seeds in suppressing the incidence of fusarium disease. This study used a completely randomized design (CRD) consisting of 5 treatments and 4 replications, namely control inoculation without endophytic bacteria, endophytic bacterial formulation with peat soil, endophytic bacterial formulation with lowland swamp soil, endophytic bacterial formulation with tidal swamp soil, bacterial formulation endophytes with kelakai and added one control inoculation treatment without endophytic bacteria and without pathogens to observe the parameters of plant height and number of tillers. Endophytic bacterial formulation treatment was able to reduce the incidence of fusarium disease. The endophytic bacterial formulation with lowland swamp soil had the lowest disease incidence of 67.5% with an effectiveness of 30.7%, the tidal swamp soil formulation 70% with an effectiveness of 28.2%, the peat soil formulation 77.5% with an effectiveness of 20.5%. % and the kelakai formulation was 82.5% with an effectiveness of 15.3%, while the control had the highest disease incidence of 97.5%. Apart from that, the endophytic bacteria formulation could extend the incubation period. Endophytic bacterial formulations can also increase plant height and number of tillers. Apart from that, soaking seeds with endophytic bacterial formulations does not affect seed germination and length of brown rice sprouts.